BASIC CONCEPT FOR ASSESMENT OF SPEAKING - Siti Sopiah; Edi Purnama; Edi Purnama (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
The aim of this paper is to know and applied the assessing of speaking in the area of school and university students is really important to practice in doing the students performance. This paper uses theory of Brown and Abeywicrama in which consist of a specific criterion is not only an appropriate task but also maximum output and a reliable scoring procedure. This paper is a library based descriptive study. The sourced has been taken from website, any source from journals and e books. The sources are read, selected, analyzed and concluded. It concludes that the assessing of speaking in the task type and testing speaking especially in the using of developing and scoring rubrics. It is suggested that the researcher, teacher, lecturer develop and update the assessment in speaking which can it can be done contextually and appropriately.